Influence of the Proximal Margin Length on Local Anastomotic Recurrence in Adenocarcinoma of the Gastroesophageal Junction: A Single-center Experience - Adel Zeinalpour; Nasser Malekpour Alamdari; Barmak Gholizadeh; Saeidreza Ghaderi; Hamed Ebrahimibagha (Iranian Journal of Colorectal Research, 2023)
Background: Curative resection with adequate margins is a treatment principle in gastroesophageal junction cancers. There is still no comprehensive agreement on the length of the negative proximal margin after total gastrectomy in Siewert II and III tumors. Extending the proximal negative margin in this anatomical region is very difficult in some cases and can cause more complications for the patients. This study aimed to investigate the influence of the negative proximal margin length on the local anastomotic recurrence in gastroesophageal junction (GEJ) adenocarcinoma in a referral cancer center in Iran.Methods: In a prospective cross-sectional study, 35 patients with GEJ Sievert II and III adenocarcinomas who underwent total radical gastrectomy from 2017 to 2020 were included. Proximal margin length was measured immediately after resection in the operation room. Then, patients were evaluated for local recurrence at the anastomosis site after two years by endoscopic examination. The relationship between negative proximal margin length, local recurrence rate, and overall survival was evaluated.Results: From 35 patients 29 (82.9%) cases had negative proximal margins, and 6 (17.1%) cases had positive proximal margins. The least negative proximal margin length was 0.1 cm, and the most were 5 cm. The mean margin was 2±1.6 cm. Based on the endoscopic and pathologic findings, the local recurrence at the anastomosis site was 20% in two years of follow-up. The incidence of local tumor recurrence was higher in patients with positive margins versus patients with negative ones (11.4% vs. 8.6%, P=0.007). There was no significant relationship between the negative proximal margin length and the incidence of local anastomotic recurrence.Conclusion: According to our findings, the length of the negative proximal margin has no effect on the rate of local recurrence at the anastomosis site, however it is suggested  to reach the negative proximal margin in all tumor stages in total gastrectomy for Siewert II and III gastric cardia tumors.